CARING THEORY IN CORRELATION TO HOSPITAL ORGANIZATIONAL CULTURE TOWARDS A SUSTAINABLE HOLISTIC PROGRAM FOR NURSES - Reyes, Jennifer P (LIFE: International Journal of Health and Life-Sciences, 2019)
The study determined the significant correlation between the extent of attainment of the Caring Theory and extent of practice of characteristic of hospital organizational culture - Leadership Style, Managerial Values and Characteristics of Members, amongst 491 nurses from 5 government-funded hospitals in Metro Manila. It also showed: a very high extent of Caring attained by the nurses in terms of all the Caritas processes except the third; a very high extent of the Characteristics of the Hospital Organizational Culture Being Practiced as to Characteristics of its Members; and a high extent as to Leadership Style, and Managerial Values. It was recommended that nurses: must be more sensitive to their needs and of others; sustain their caring attitude and observe well characterization of others; lastly to enhance their leadership style and managerial values; Hospital administrators must arrange for ideal nurse-patient ratio and give nurses the appropriate load that they can accomplish for the shift; They also have to create a culture of success and positive environment for their nurses and lastly they should use the Sustainable Holistic Program for Nurses to sustain their very high extent of practice of caring attitudes and enhance those that were not.